Increasing maternal age associates with lower placental CPT1B mRNA expression and acylcarnitines, particularly in overweight women - Yong, Hannah E. J.; Watkins, Oliver C.; Mah, Tania K. L.; Cracknell-Hazra, Victoria K. B.; Pillai, Reshma Appukuttan; Selvam, Preben; Islam, Mohammad O.; Sharma, Neha; Cazenave-Gassiot, Amaury; Bendt, Anne K.; Wenk, Markus R.; Godfrey, Keith M.; et al. (Frontiers in Physiology, 2023)
Older pregnant women have increased risks of complications including gestational diabetes and stillbirth. Carnitine palmitoyl transferase (CPT) expression declines with age in several tissues and is linked with poorer metabolic health. Mitochondrial CPTs catalyze acylcarnitine synthesis, which facilitates fatty acid oxidization as fuel. We hypothesized that the placenta, containing maternally-inherited mitochondria, shows an age-related CPT decline that lowers placental acylcarnitine synthesis, increasing vulnerability to pregnancy complications. We assessed CPT1A, CPT1B, CPT1C and CPT2 mRNA expression by qPCR in 77 placentas and quantified 10 medium and long-chain acylcarnitines by LC-MS/MS in a subset of 50 placentas. Older maternal age associated with lower expression of placental CPT1B, but not CPT1A, CPT1C or CPT2. CPT1B expression positively associated with 8 acylcarnitines and CPT1C with 3 acylcarnitines, CPT1A negatively associated with 9 acylcarnitines, while CPT2 did not associate with any acylcarnitine. Older maternal age associated with reductions in 5 acylcarnitines, only in those with BMI≥ 25kg/m2, and not after adjusting for CPT1B expression. Our findings suggest that CPT1B is the main transferase for placental long-chain acylcarnitine synthesis, and age-related CPT1B decline may underlie decreased placental metabolic flexibility, potentially contributing to pregnancy complications in older women, particularly if they are overweight.